2022
DOI: 10.3390/jcm11030655
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of the Alter miR let-7a and miR-335 Expression Level Regulating the CCR7/CCL19 Axis as Potential Biomarkers of Tumor Progression in NSCLC

Abstract: The chemokine receptor 7/C-C ligand 19 chemokine (CCR7/CCL19) has been implicated in the development and progression of NSCLC. Its expression is regulated by various epigenetic factors including miRNAs. The aim of this study was to assess the expression of CCR7/CCL19 in cancer tissue in relation to that of miRNAs (miR-let-7a, miR-335) as transcriptional regulators. The expression of the tested miRNAs was also evaluated in serum exosomes. Sixty patients (n = 60) were enrolled in the study. The total expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 52 publications
1
1
0
Order By: Relevance
“…However, during tumorigenesis, the expression level of CCR6 mRNA decreased, in contrast to the expression level of CCR7 mRNA. We have also demonstrated this relationship in previous studies 35 . We confirmed that specific and differential pattern of CCR6 , CCR7 mRNA expression levels was manifested in NSCLC tumor cells.…”
Section: Discussionsupporting
confidence: 84%
“…However, during tumorigenesis, the expression level of CCR6 mRNA decreased, in contrast to the expression level of CCR7 mRNA. We have also demonstrated this relationship in previous studies 35 . We confirmed that specific and differential pattern of CCR6 , CCR7 mRNA expression levels was manifested in NSCLC tumor cells.…”
Section: Discussionsupporting
confidence: 84%
“…A recent study confirmed that miR-335 and miR let-7a expression levels in the serum of patients with NSCLC correlated with lymph node metastasis. Therefore, these miRNAs may potentially serve as non-invasive molecular biomarkers to predict metastasis in liquid biopsy [ 14 ]. In recent years, PIWI-interacting RNAs (piRNAs) are emerging as crucial players in cancer genomics.…”
mentioning
confidence: 99%